Implementation of the academic supervision policy by school principals in enhancing the pedagogical competence of class teachers - Natuna, Daeng Ayub; Adi Putra, Muhammad Jaya; Pakpahan, Tresia (Universitas Negeri Semarang, 2023)
Qualified teachers have responsibilities, tasks, functions, and significant roles in shaping students' future abilities. Through the implementation of academic supervision, schools aim to enhance one aspect of teacher competence, which is pedagogical competence. The objectives of this research are to describe and analyze the planning, implementation, evaluation, and follow-up actions of the school principal in implementing academic supervision, as well as to describe and analyze the pedagogical competence of class teachers at Esa Sejahtera Primary School Pekanbaru. The implementation research design with a qualitative approach. The data sources collected and used include primary data and secondary data. Data collection techniques involve document review, summarizing observation results, and condensing interview findings from sources or informants. The result of the research shows that: The planning of academic supervision policy is categorized as very good. The implementation, evaluation and the follow up of academic supervision policy is categorized as good. The pedagogical competence of class teachers at Esa Sejahtera Primary School in Pekanbaru is categorized as good. Teachers need to understand educational concepts or foundations, an understanding of the physical, psychological, social, and emotional characteristics of students, the ability to develop the curriculum and syllabus, design instruction, conduct educational and dialogical teaching, utilize instructional technology, perform learning outcome assessments, and foster student development by actualizing various potentials they possess. This research contributes valuable insights into the academic supervision process and pedagogical competence, offering practical implications for educational management and teacher development. Its novel approach and localized focus make it a significant addition to the field of educational research.